L’Attestation d’études collégiales en assurance de dommages - Fortin, Denyse (Assurances, 1994)
As Director of Admissions and Training at the lnsurance Brokers Association of the Province of Québec, the author is well-placed to describe the new property insurance program for market intermediaries which entitles students to a Diploma of Collegiate Studies. Mrs. Fortin briefly describes how the program came to be, examines its contents and discusses how well it meets the needs of Québec's property insurance market. In her conclusion, Mrs. Fortin states that this specialized program will give graduates the necessary tools to face the challenges of today and tomorrow.